Fine Scale Assemblage Structure of Benthic Invertebrate Megafauna on the North Pacific Seamount Mokumanamana - Morgan, Nicole B.; Goode, Savannah; Roark, E. Brendan; Baco, Amy R. (Frontiers in Marine Science, 2019)
Changes in benthic megafaunal assemblage structure have been found across gradients of environmental variables for many deep-sea habitats, but patterns remain under-investigated on seamounts. To assess the extent of variability in benthic communities at the scale of within a single seamount, and to assess environmental drivers of assemblage changes, Mokumanamana, also known as Necker Island, a seamount in the Papahānaumokuākea Marine National Monument with no known history of human impacts, was surveyed. Replicate 1 km transects were conducted along depth contours at 50 m depth intervals from 200 – 700 m on three sides of Mokumanamana using the AUV Sentry. Megafaunal abundance and substrate parameters were obtained from 26,119 total images. The dominant megafaunal taxa were sponges, corallimorpharians, cup corals, and benthic ctenophores. Sea pens and alcyonacean octocorals were also abundant. Overall, abundance and diversity of megafauna increased with depth. Beta-diversity through species substitution with depth was very high. Beta-diversity was also high between the sides and likewise defined almost exclusively by species substitution. Crossed ANOSIM by depth and side showed community structure differed on Mokumanamana for both factors. NMDS and cluster analyses of Mokumanamana show nine assemblages that were defined by depth and reflect differences between sides of the seamount. Environmental modeling with DISTLM indicates sediment, oxygen, substrate variability and roughness, POC, and surface currents are correlated with these assemblage differences. These results suggest that microhabitats on seamounts can promote unique assemblages along depth gradients as well as on different sides of a feature, and this diversity may be easily overlooked without fine-scale sampling. These findings have implications for management and conservation of seamounts as well as future ecological studies of seamounts, as seamounts are generally sampled on much coarser spatial scales.